2014
DOI: 10.1016/j.molcel.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Necessary and Sufficient Role for a Mitosis Skip in Senescence Induction

Abstract: Senescence is a state of permanent growth arrest and is a pivotal part of the antitumorigenic barrier in vivo. Although the tumor suppressor activities of p53 and pRb family proteins are essential for the induction of senescence, molecular mechanisms by which these proteins induce senescence are still not clear. Using time-lapse live-cell imaging, we demonstrate here that normal human diploid fibroblasts (HDFs) exposed to various senescence-inducing stimuli undergo a mitosis skip before entry into permanent ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
171
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(190 citation statements)
references
References 41 publications
16
171
0
Order By: Relevance
“…The Nakanishi group showed that replicative senescence or exposure to various senescence-causing stimuli induces p53-dependent mitotic bypass (referred to as mitotic skipping), entailing irreversible cell cycle arrest in the 4N G1 state and accumulation of the senescent markers p16 and b-galactosidase. 93 Moreover, stable G2 arrest induced by ionizing radiation (IR) was associated with p53/p21-dependent premature APC/C Cdh1 activation and degradation of mitotic cyclins, consistent with previous observations. [74][75][76] However, unlike p53-mediated mitotic bypass, APC/C Cdh1 activation alone does not appear to be sufficient to induce senescence, that additionally requires repression of mitotic regulators by pRb family pocket proteins (Fig.…”
Section: Senescence In G2 -An Old Concept Awaiting Wider Recognitionsupporting
confidence: 89%
See 3 more Smart Citations
“…The Nakanishi group showed that replicative senescence or exposure to various senescence-causing stimuli induces p53-dependent mitotic bypass (referred to as mitotic skipping), entailing irreversible cell cycle arrest in the 4N G1 state and accumulation of the senescent markers p16 and b-galactosidase. 93 Moreover, stable G2 arrest induced by ionizing radiation (IR) was associated with p53/p21-dependent premature APC/C Cdh1 activation and degradation of mitotic cyclins, consistent with previous observations. [74][75][76] However, unlike p53-mediated mitotic bypass, APC/C Cdh1 activation alone does not appear to be sufficient to induce senescence, that additionally requires repression of mitotic regulators by pRb family pocket proteins (Fig.…”
Section: Senescence In G2 -An Old Concept Awaiting Wider Recognitionsupporting
confidence: 89%
“…Active pRb inhibits the expression of genes that control G2/M progression, leading to irreversible G2 arrest of the cell cycle. It is proposed that p53 might induce senescence independently of p21 93 through mechanisms that are not fully clear. Like in G1 arrest, p16 stabilizes senescence in G2 presumably by targeting pRb kinases.…”
Section: Senescence In G2 -An Old Concept Awaiting Wider Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that binucleated cells can be divided into two types: reversible and irreversible. Johmura et al (2014) showed that normal human diploid fibroblasts exposed to various senescence-inducing stimuli Serum-free examination Medium improvement examination Fig. 5 Results of the serum-free and the medium improvement examinations.…”
Section: Discussionmentioning
confidence: 99%